2019
DOI: 10.1038/s41598-019-44764-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast and reliable advanced two-step pore-size analysis of biomimetic 3D extracellular matrix scaffolds

Abstract: The tissue microenvironment is a major contributor to cellular functions, such as cell adhesion, migration and invasion. A critical physical parameter for determining the effect of the microenvironment on cellular functions is the average pore-size of filamentous scaffolds, such as 3D collagen fiber matrices, which are assembled by the polymerization of biopolymers. The scaffolds of these matrices can be analyzed easily by using state-of-the-art laser scanning confocal imaging. However, the generation of a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…an advanced pore size analysis ( Figure 4B), published previously (Fischer et al, 2019). We found that all observed collagen compositions featured networks with significantly decreasing pore sizes by increasing collagen concentrations ( Supplementary Table S2) (p = 0.01, or less for R collagens, p = 0.05 or less for RB and B collagens).…”
Section: Collagen Composition Influences Structural Characteristics Osupporting
confidence: 72%
See 2 more Smart Citations
“…an advanced pore size analysis ( Figure 4B), published previously (Fischer et al, 2019). We found that all observed collagen compositions featured networks with significantly decreasing pore sizes by increasing collagen concentrations ( Supplementary Table S2) (p = 0.01, or less for R collagens, p = 0.05 or less for RB and B collagens).…”
Section: Collagen Composition Influences Structural Characteristics Osupporting
confidence: 72%
“…The pore size is another crucial parameter to determine structural traits (Fischer et al, 2019). Concerning confined scaffolds with spatial hindrances the pore size is a key value for describing a fibrillary network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the channels are too narrow for the nucleus to pass, the T cells would appear to halt at the position until the matrix breaks loose or until they manage to squeeze themselves out. According to the experimentally determined pore size distribution in collagen matrices with various concentration [40], one can estimate that the average pore diameter is around 7.5 µm for collagen density 2 mg/ml. The diameter distribution is broad enoughto have some pores with diameter around 9 µm, where T cells with diameter 10 µm can squeeze through without deforming the surrounding collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
“…show a persistent motion for all collagen concentrations, slow T cells perform anti-persistent motion in 2 mg/ml collagen and become persistent in denser ones. A possible explanation is that the average pore size increases with decreasing collagen density [40] which implies that for low collagen densities, T cells can more easily find some pores around them that are large enough to get into them; this might allow slow T cells to change their direction when they face a constriction while creating a channel. This is, however, less probable in denser collagens, as most pores are smaller than T cells and need equal effort to pass.…”
Section: B the Two-state Motility Typementioning
confidence: 99%